Physical and Chemical Characterisation of the Pigments of a 17th-Century Mural Painting in the Spanish Caribbean - Virginia Flores-Sasso (MDPI AG, 2021)
The arrival of Spaniards in the Caribbean islands introduced to the region the practice of applying pigments onto buildings. The pigments that remain on these buildings may provide data on their historical evolution and essential information for tackling restoration tasks. In this study, a 17th-century mural painting located in the Cathedral of Santo Domingo on the Hispaniola island of the Caribbean is characterised via UV–VIS–NIR, Raman and FTIR spectroscopy, XRD and SEM/EDX. The pigments are found in the older Chapel of Our Lady of Candelaria, currently Chapel of Our Lady of Mercy. The chapel was built in the 17th century by black slave brotherhood and extended by Spaniards. During a recent restoration process of the chapel, remains of mural painting appeared, which were covered by several layers of lime. Five colours were identified: ochre, green, red, blue and white. Moreover, it was determined that this mural painting was made before the end of the 18th century, because many of the materials used were no longer used after the industrialisation of painting. However, since both rutile and anatase appear as a white pigment, a restoration may have been carried out in the 20th century, and it has been painted white.